2007
DOI: 10.1074/jbc.m701182200
|View full text |Cite
|
Sign up to set email alerts
|

The Src-like Adaptor Protein 2 Regulates Colony-stimulating Factor-1 Receptor Signaling and Down-regulation

Abstract: The colony-stimulating factor 1 receptor 4 is a member of the type III receptor tyrosine kinase (RTK) family, which includes c-Kit, platelet-derived growth factor receptor ␣ and ␤, and Flt3 (1). All of the functions of colony-stimulating factor-1 (CSF-1) are mediated by CSF-1R, which is the primary regulator of the common myeloid lineage consisting of osteoclasts and mononuclear phagocytes (monocytes and macrophages) in vivo (2-5).Ligand binding induces CSF-1R dimerization and autophosphorylation on tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 38 publications
2
43
2
Order By: Relevance
“…The ability of SLAP to be induced under particular circumstances suggests that it may regulate multiple receptors and pathways. Previous studies from our group and other investigators showed that SLAP2 binds to and regulates M-CSFR and CSF-1R; expression of dominant negative SLAP2 results in a potentiation of CSF-1-mediated differentiation (14,16). Similar to the situation in T cells, these effects also seem to be mediated through c-Cbl (14).…”
Section: Endritic Cells (Dc)supporting
confidence: 50%
See 4 more Smart Citations
“…The ability of SLAP to be induced under particular circumstances suggests that it may regulate multiple receptors and pathways. Previous studies from our group and other investigators showed that SLAP2 binds to and regulates M-CSFR and CSF-1R; expression of dominant negative SLAP2 results in a potentiation of CSF-1-mediated differentiation (14,16). Similar to the situation in T cells, these effects also seem to be mediated through c-Cbl (14).…”
Section: Endritic Cells (Dc)supporting
confidence: 50%
“…Although many SLAP-and SLAP2-binding partners have been mapped to the SH2 domain (9)(10)(11)(12)(13)(14), we found that SLAP interacted with the a subunit of GM-CSFR, which, in the mouse, does not contain any potential tyrosine-phosphorylation sites within the cytoplasmic tail. However, GM-CSFRa contains a PXXP motif that may mediate SH3 domain interactions (34,35).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations